2003
DOI: 10.1242/dev.00662
|View full text |Cite
|
Sign up to set email alerts
|

Tracing ofher5progeny in zebrafish transgenics reveals the dynamics of midbrain-hindbrain neurogenesis and maintenance

Abstract: The midbrain-hindbrain domain (MH) of the vertebrate embryonic neural tube develops in response to the isthmic organizer (IsO), located at the midbrain-hindbrain boundary (MHB). MH derivatives are largely missing in mutants affected in IsO activity; however, the potentialities and fate of MH precursors in these conditions have not been directly determined. To follow the dynamics of MH maintenance in vivo, we used artificial chromosome transgenesis in zebrafish to construct lines where egfp transcription is dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 44 publications
(77 reference statements)
4
76
0
Order By: Relevance
“…These results add to our previous observation that the early MHB progenitor pool generates cells populating r1 and r2 (and possibly also, to a low extent, r3 and r4; Tallafuss and Bally-Cuif, 2003). They also extend fate mapping data for Wnt1-positive cells in the embryonic day (E) 7.5 mouse embryo that gave rise to a few 5HT neurons of the anterior raphe (Zervas et al, 2004).…”
Section: Pet1-positive Cells Located In R1-2 Originate From the Mhb Psupporting
confidence: 82%
See 3 more Smart Citations
“…These results add to our previous observation that the early MHB progenitor pool generates cells populating r1 and r2 (and possibly also, to a low extent, r3 and r4; Tallafuss and Bally-Cuif, 2003). They also extend fate mapping data for Wnt1-positive cells in the embryonic day (E) 7.5 mouse embryo that gave rise to a few 5HT neurons of the anterior raphe (Zervas et al, 2004).…”
Section: Pet1-positive Cells Located In R1-2 Originate From the Mhb Psupporting
confidence: 82%
“…Because previous results from our laboratory also suggested that the MHB progenitor pool contributed neurons to the ventral anterior hindbrain (Tallafuss and Bally-Cuif, 2003), we specifically tested for the contribution of this pool to r1-2 serotonergic precursors. We used her5PAC:egfp transgenic embryos, which allow us to locate the early MHB pool by GFP expression at late gastrulation.…”
Section: Pet1-positive Cells Located In R1-2 Originate From the Midbrmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, we performed in situ hybridization with several genes known to be expressed in pouch endoderm, such as her5 (Fig. 6F,G ;Tallafuss and Bally-Cuif, 2003), foxa3, which is expressed in endoderm and axial mesendoderm (Warga and Kane, 2003), as well as sox17, a panendodermal marker (data not shown; Alexander and Stainier, 1999). We did not detect any obvious changes in the number of cells expressing these genes (Fig.…”
Section: Ra Does Not Play a Role In Pharyngeal Endoderm Specificationmentioning
confidence: 84%